Analisis Pengaruh PAD, DAU, dan DAK terhadap PDRB Kabupaten/Kota di Provinsi Aceh - Fajar Hidayat; Muhammad Nasir (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2026)
This study aims to analyze the effects of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK) on the Gross Regional Domestic Product (GRDP) of regencies/municipalities in Aceh Province during the period 2017–2024. The research employs a quantitative approach using panel data regression with the Fixed Effect Model (FEM). The results indicate that, partially, PAD, DAU, and DAK have positive and significant contributions to the growth of GRDP. The simultaneous synergy of these three variables also demonstrates a significant effect, confirming that fiscal instruments play a crucial role as key drivers of the regional economic structure. Therefore, local governments are expected to optimize PAD and effectively integrate the management of intergovernmental transfer funds to stimulate productive expenditure that directly strengthens economic performance across regencies/municipalities in Aceh Province.